An attack on science? Media use, trust in scientists, and perceptions of global warming - Hmielowski, Jay D.; Feldman, Lauren; Myers, Teresa A.; Leiserowitz, Anthony; Maibach, Edward (Public understanding of science (Bristol, England), 2014)
There is a growing divide in how conservatives and liberals in the USA understand the issue of global warming. Prior research suggests that the American public’s reliance on partisan media contributes to this gap. However, researchers have yet to identify intervening variables to explain the relationship between media use and public opinion about global warming. Several studies have shown that trust in scientists is an important heuristic many people use when reporting their opinions on science-related topics. Using within-subject panel data from a nationally representative sample of Americans, this study finds that trust in scientists mediates the effect of news media use on perceptions of global warming. Results demonstrate that conservative media use decreases trust in scientists which, in turn, decreases certainty that global warming is happening. By contrast, use of non-conservative media increases trust in scientists, which, in turn, increases certainty that global warming is happening.